ONLINESHOP SEBAGAI CARA BELANJA DI KALANGAN MAHASISWA FISIP UNIVERSITAS RIAU - Gunawan, Randy; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This thesis was submitted to meet the requirements for a bachelor's degree in sociology with the title "OnlineShop as a Way of Shopping Among Students of the Faculty of Social Sciences, Riau University". The problems discussed in this thesis are how the OnlineShop phenomenon that occurs among physics students in fulfilling their needs and what factors cause students to choose how to shop through an OnlineShop to meet their needs. The subjects in this study were 7 people. The sampling technique used in this study was the snowball technique, this technique was to determine the first sample and the subsequent samples obtained from the first sample information. This method used is a qualitative research method because this method describes every problem regarding this title descriptively. The data filtering instruments used are observations, questionnaires, and documents. The theory used is the theory of socio-cultural change and the theory of consumptive behavior. that the OnlineShop among the Riau University Fisip students provides various changes in the way of shopping. These changes are not only in terms of shopping patterns but there are also very visible changes, namely changes in the use of OnlineShops for some students who tend to always use OnlineShops as a way of shopping to meet their needs. OnlineShops have replaced many conventional shopping models into OnlineShops. The OnlineShop provides various conveniences so that fromKeywords: OnlineShop, A way Shopping, Fisip student of Universitas Riau Â